2020
DOI: 10.1074/jbc.ra119.010868
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides released from palmitate-activated murine macrophages attract neutrophils

Abstract: Obesity and elevation of circulating free fatty acids are associated with an accumulation and proinflammatory polarization of macrophages within metabolically active tissues, such as adipose tissue, muscle, liver, and pancreas. Beyond macrophages, neutrophils also accumulate in adipose and muscle tissues during high-fat diets and contribute to a state of local inflammation and insulin resistance. However, the mechanisms by which neutrophils are recruited to these tissues are largely unknown. Here we used a cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
(75 reference statements)
0
23
0
Order By: Relevance
“…Moreover, the authors found that palmitate upregulated Panx1-channel expression in macrophages mediating neutrophil attraction by release of nucleotides such as ATP. The thereby following purinergic receptor stimulation and signaling induces neutrophil migration (Tam et al, 2020). These results emphasize the role of Panx1 in neutrophil recruitment and its contribution to inflammatory response during obesity.…”
Section: Panx1 In Leukocyte Recruitment During Acute Inflammationmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, the authors found that palmitate upregulated Panx1-channel expression in macrophages mediating neutrophil attraction by release of nucleotides such as ATP. The thereby following purinergic receptor stimulation and signaling induces neutrophil migration (Tam et al, 2020). These results emphasize the role of Panx1 in neutrophil recruitment and its contribution to inflammatory response during obesity.…”
Section: Panx1 In Leukocyte Recruitment During Acute Inflammationmentioning
confidence: 67%
“…Recently, Tam et al (2020) demonstrated that during metabolic inflammation pro-inflammatory macrophages release chemotactic factors upon exposure to saturated fatty acids, such as palmitate, which was associated with recruitment and infiltration of neutrophils into adipose tissues. Heat inactivation or proteinase K digestion of media released by fatty acid treated macrophages did not alter neutrophil recruitment but was effective to inhibit CXCL-1 induced chemotaxis suggesting that these macrophage derived chemotactic factors are not proteins (Tam et al, 2020). Moreover, the authors found that palmitate upregulated Panx1-channel expression in macrophages mediating neutrophil attraction by release of nucleotides such as ATP.…”
Section: Panx1 In Leukocyte Recruitment During Acute Inflammationmentioning
confidence: 99%
“…This may promote the recruitment of neutrophils into obese AT. 50 These results indicate that in diet-induced obesity, neutrophils quickly infiltrate the abdominal AT and cause chronic inflammation.…”
Section: Immune Cells In Obese Adipose Tissue Inflammationmentioning
confidence: 88%
“…In obese adipose tissue, decreased ILC2 cells are associated with decreased local eosinophil numbers. Finally, the recruitment of neutrophils into adipose tissue increases in obesity, and factors released from neutrophil granules, such as neutrophil elastase and myeloperoxidase, can contribute to the development of insulin resistance (Talukdar et al 2012;Tam et al 2020).…”
Section: Mechanisms Of Macrophage Accumulationmentioning
confidence: 99%